Cybersecurity in the Age of IoT and Developing Frameworks for Securing Smart Devices and Networks - Eli Ratih Rahayu; Ariesya Aprillia; Ramzi Zainum Ikhsan; Alfri Adiwijaya; Aryan Kumara (Pandawan Sejahtera Indonesia, 2025)
The rapid proliferation of the Internet of Things (IoT) has significantly transformed various industries, enhancing automation and efficiency. However, it has also brought forth substantial cybersecurity challenges that threaten data integrity, user privacy, and system reliability. This study proposes a multi-layered cybersecurity framework to address these vulnerabilities by integrating robust security measures such as device authentication, data encryption, continuous network monitoring, and enhanced privacy protection. Employing a mixed methods research approach, the framework was rigorously validated through real world implementation in smart home environments, demonstrating tangible improvements in security resilience. Notably, the findings indicate a 40% reduction in threat response time, a 96% intrusion detection rate, and the complete elimination of data breaches post-implementation, emphasizing the framework’s effectiveness in mitigating cyber risks. Proactively addressing security concerns, this study provides valuable insights for key stakeholders, including device manufacturers, network operators, and policymakers, guiding them toward implementing stringent cybersecurity protocols to enhance trust and compliance across IoT ecosystems. Furthermore, the results highlight the necessity for continuous adaptation and innovation in cybersecurity strategies, ensuring that IoT deployments remain resilient against evolving cyber threats. As IoT adoption continues to accelerate across sectors such as healthcare, smart cities, and industrial automation, this research underscores the critical importance of a proactive, comprehensive security approach to safeguard connected infrastructures. Ultimately, the proposed framework serves as a blueprint for strengthening IoT security governance and fostering a safer digital ecosystem, reinforcing the importance of collaborative efforts in securing the future of interconnected technologies.